Margaret's monsters - Heyes, Michael E., author.
1 online resource
Keywords: "St. Margaret of Antioch was one of the most popular saints in medieval England and, throughout the Middle Ages, the various Lives of St. Margaret functioned as a blueprint for a virginal life and supernatural assistance to pregnant women during the dangerous process of labor. In her narrative, Margaret is accosted by various demons and, having defeated each monster in turn, she is taken to the place of her martyrdom where she prays for supernatural boons for her adherents. This book argues that Margaret's monsters are a key element in understanding Margaret's importance to her adherents, specifically how the sexual identities of her adherents were constructed and maintained"--